MAICSA 1959-1999 40th anniversary (Tokyo : Mitsubishi Chemical Corporation)
Explained on the background of The Malaysian Association of the Chartered Secretaries and Administrators, and its mission, history and development from 1959 to 1999
Keywords: Industrial management -- Malaysia; Corporation Secretaries -- Malaysia